Rural youth in recent wars: an agrarian perspective on coastal West Africa - (:unkn) unknown (My University, 2007)
The contribution aims at opening up the possibility of a more coherent regional analysis of recent West African conflicts. Civil wars broke out in several coastal Western African countries from the late 1980s. Liberia, Sierra Leone and Côte d’Ivoire all fall within the Upper Guinean rainforest block and all three civil wars shared personnel. Whether they have common causes is more contentious. Here, we accept as a starting point that all three conflicts had their own internal and external dynamics. But we will also argue that there are some common elements of an agrarian nature which specially affect the involvement of young people in the conflicts. In Sierra Leone and Liberia, the fighting was mainly in rural areas and involved mainly rural youth. Tensions over land link the conflicts in Liberia and Cote d’Ivoire. The land issue seems at first sight more tenuous in Sierra Leone. Probing the social background and motivation of ex-combatants in Sierra Leone, however, reveals important but largely hidden tensions concerning labour utilization and land access, which when fully analysed suggest parallels with the other two recent civil wars in the region. The paper falls in two main parts. Part one presents a broad-brush, long duree, model of agrarian transformation within the Upper Guinean Forests of West Africa. In order to explain aspects of agrarian trajectories underpinning conflict in the region we differentiate between models of the so-called “lineage mode of production”. These different models are useful, we argue, in focusing attention on the different ways in which agrarian variables present themselves as factors in youth involvement in recent conflicts - armed groups in Liberia and Sierra Leone, patriotic vigilante groups and inter-community tensions in southern rural Côte d’Ivoire. Part two offers a more detailed analysis of two case-study regions – eastern Sierra Leone and central-western CI. Accounting for social breakdown leadi
Keywords: African Research